INSIDENSI PENYAKIT TUNGRO PADA TANAMAN PADI SAWAH DI KECAMATAN TOMOHON BARAT KOTA TOMOHON - Livita C. Tamuntuan; Guntur S.J. Manengkey; Henny V.G. Makal; Max M. Ratulangi (Universitas Sam Ratulangi, 2015)
ABSTRACTThis research aims to study the incidence of disease in lowland rice tungro held in the District of West Tomohon, and lasted for 5 months from the month of November 2014 until March 2015. This study uses a survey or field observation purposive sampling with the object of research fields rice farmers in West Tomohon sub district, which is in the Village Taratara and Village Woloan. Each village was taken three plots groves and each plot was made sliced diagonally with five subplots with the size of each subplot that is 2 m x 2 m. At each subplot obtained 56 family of plants that was four weeks with a spacing of 15 cm x 20 cm x 40 cm (Legowo row 1: 3) of crop land, observations were made four times at intervals of one week. The results showed that characterizes the disease tungro rice paddy in the district of West Tomohon is infected plants tungro disease suffered stunted plant growth (dwarf), the color of the leaves turn yellow to yellow orange accompanied with brown spots on the leaves. Tungro disease incidence in rice crops in West Tomohon sub district amounted to 22:43%. Tungro disease vector Populations in West Tomohon sub district is 7.6 tail.Key words: Incidence, Disease Tungro, Rice